2012
DOI: 10.4103/0970-4388.95592
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis: A report of two pediatric cases and a brief review

Abstract: Oral submucous fibrosis is a chronic debilitating disorder which is usually seen in adults with areca nut chewing habit. A rapid upsurge in the popularity of commercial areca nut products, especially among the younger generation, is a cause of grave concern, as satisfactory management is still lacking. Hereby, two pediatric cases of oral submucous fibrosis are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…22 Dhariwal et al demonstrated 2 cases of Indian OSF in children, specifically, a 10-year-old boy with a history of chewing gutkha and a 12-year-old girl with a history of chewing pan masala. 23 Shah et al reported an 11-year-old Bangladeshi girl with OSF who had a history of chewing areca nut and supari. 24 Chaturvedi et al found that patients with oral cancer caused by OSF were younger than non-OSF patients, 25 suggesting that children chewing areca nut could suffer from OSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Dhariwal et al demonstrated 2 cases of Indian OSF in children, specifically, a 10-year-old boy with a history of chewing gutkha and a 12-year-old girl with a history of chewing pan masala. 23 Shah et al reported an 11-year-old Bangladeshi girl with OSF who had a history of chewing areca nut and supari. 24 Chaturvedi et al found that patients with oral cancer caused by OSF were younger than non-OSF patients, 25 suggesting that children chewing areca nut could suffer from OSF.…”
Section: Discussionmentioning
confidence: 99%
“…Agrawal et al reported a case of OSF in a 9‐year‐old Indian girl with a history of chewing areca nut . Dhariwal et al demonstrated 2 cases of Indian OSF in children, specifically, a 10‐year‐old boy with a history of chewing gutkha and a 12‐year‐old girl with a history of chewing pan masala . Shah et al reported an 11‐year‐old Bangladeshi girl with OSF who had a history of chewing areca nut and supari .…”
Section: Discussionmentioning
confidence: 99%
“…10 Table 1 shows the details of OSMF patients reported in Pediatric age group all over world till date. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Reviewing the literature no case has been reported with an interincisal opening less than 10 mm, 24 thus making this case to be the first incident case of OSMF in a child with least interincisal opening of 06 mm.…”
Section: Discussionmentioning
confidence: 99%
“…28 Homogeneous variety of leukoplakia is characterized by uniformly flat, thin, uniformly white in appearance and shows a shallow crack on the surface of the whitish patch. 28 Non-homogeneous variety is defined as a white and red lesion called as erythroleukoplakia which often irregularly flat (speckled) or nodular. Verrucous leukoplakia is other types of non-homogeneous leukoplakia.…”
Section: Clinical Presentationsmentioning
confidence: 99%